THE NARRATIVE ACT: WITTGENSTEIN AND NARRATOLOGY - McDonald, Henry (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
This essay uses the late work of Ludwig Wittgenstein to reformulate the traditional distinction between story and narrative discourse, or diegetic and extra-diegetic levels of narrative, as a distinction between story and narrative act. In describing the transformations performed by the narrative act, the author elaborates the principle of narrative uncertainty, which dictates that the more definite the account of story or plot, the more indefinite the account of the narrative act — and vice versa. In this conceptual framework, the essay then characterizes the narrative act as the differential, within a given fictional text, of two of more types of stories (or plots), and articulates the relationship between narrative act, narrator, and cultural context.